Integrating Malay Local Wisdom into Pancasila Student Profile Strengthening Project: Development of 'Pekasam' Theme Teaching Materials - Nazri, Nazri; Putra, M. Jaya Adi; Marhadi, Hendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2026)
This study aimed to develop and validate a pekasam-themed module integrating Riau Malay local wisdom into the Pancasila Student Profile (P5) project. Using a Research and Development (R&D) design with the ADDIE model, the study involved 30 sixth-grade students and three teachers at SDN 012 Lalang Kabung, Riau. Data were collected through observation, questionnaires, expert validation, and documentation, analyzed with Aiken’s V for validity and Cronbach’s Alpha for reliability. Findings showed that independence (3.17; 73% high) and creativity (2.97) were strengthened, while collaboration (2.87) and critical reasoning (2.83) remained weaker; student enthusiasm for local culture was very high (4.0). Expert validation confirmed strong content and language quality (0.83) but indicated the need for refinement in visual aspects (0.67–0.75). In conclusion, culture-based project learning effectively nurtures autonomy and identity, though collaboration and critical reasoning require further pedagogical support. This study contributes a practical model of culturally responsive pedagogy aligned with national character education and global deep learning frameworks, with future research advised to test its adaptability across regions and long-term impacts.